DIC Score Combined With CLIF-C OF Score Is More Effective in Predicting Prognosis in Patients With Hepatitis B Virus Acute-on-Chronic Liver Failure - Zhang, Xueyun; Han, Jiajia; Qi, Xun; Zhang, Yao; Zhou, Pu; Liu, Xiaoqin; Ying, Yue; Zhang, Wenhong; Zhang, Jiming; Huang, Yuxian (Frontiers in Medicine, 2022)
Abstract Coagulation and fibrinolysis disorders are major prognostic factors in hepatitis B virus-related acute-on-chronic liver failure (HBV-ACLF) patients. Here, we aimed to clarify the role of disseminated intravascular coagulation (DIC) scores in predicting HBV-ACLF patient prognosis. We assessed the DIC score from HBV-ACLF patients at Huashan Hospital in Shanghai, China from June 2013 to May 2021 and evaluated it in relation to short-term mortality, clinical course, and infection. A novel prognostic scoring model was proposed based on DIC scores. A total of 163 transplant-free HBV-ACLF patients were enrolled. DIC scores were higher in non-survivors than survivors (6 vs. 4, P = 0.000) and were independently associated with short-term mortality [hazard ratio (HR): 1.397, 95% confidence interval (95% CI): 1.040–1.875, P = 0.026]. DIC scores were associated with ACLF grade, clinical course, and infection. Moreover, they were correlated with model for end-stage liver disease (MELD) scores (r = 0.521, P < 0.001). The area under the receiver operating curve (auROC) of CLIF-C OF-DICs [a novel prognostic score based on age, DIC score, and Chronic liver failure-consortium organ function score (CLIF-C OFs)] for 90-day mortality was 0.936, which was higher than six other generic prognostic scoring models. These results were confirmed in a validation cohort (n = 82). In conclusion, elevated DIC score is associated with poor prognosis in HBV-ACLF patients, and can be used jointly with CLIF-C OFs to improve the accuracy of prognosis prediction.